2022
DOI: 10.33019/agrosainstek.v6i1.202
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Korelasi dan Sidik Lintas Karakter Pertumbuhan dan Komponen Hasil terhadap Hasil Bawang Merah (Alllium Cepa L. Var Aggregatum) di Dataran Tinggi

Abstract: Komoditas bawang merah merupakan komoditas strategis dan memiliki nilai ekonomis tinggi serta tidak dapat disubstitusi dengan komoditas lain. Penelitian dilakukan untuk mengetahui korelasi dan pengaruh langsung dan tidak langsung antara karakter pertumbuhan dan komponen hasil terhadap hasil bawang merah di dataran tinggi. Penelitian dilakukan dari bulan September sampai dengan November 2019 di Lembang (Kab. Bandung Barat), Pacet (Kab. Bandung), dan Samarang, (Kab. Garut). Materi penelitian ini meliputi 12 geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In rice, traits of productive tillers number and total grain number have a direct and positive effect on yield (Kartina et al, 2016). Waluyo et al (2022) showed that traits of leaf length have a very high positive direct effect on the yield of wet bulbs per hectare in onions. The foliage attitude and leaf spines traits could be selected as criteria to improve flesh thickness trait, and peduncle length could be selected to improve pineapple fruit weight (Nasution, 2018).…”
Section: Maizementioning
confidence: 99%
“…In rice, traits of productive tillers number and total grain number have a direct and positive effect on yield (Kartina et al, 2016). Waluyo et al (2022) showed that traits of leaf length have a very high positive direct effect on the yield of wet bulbs per hectare in onions. The foliage attitude and leaf spines traits could be selected as criteria to improve flesh thickness trait, and peduncle length could be selected to improve pineapple fruit weight (Nasution, 2018).…”
Section: Maizementioning
confidence: 99%